Trade-off between seed number and weight: Influence of a grass–endophyte symbiosis - Gundel, Pedro Emilio (2012)
Plant fitness is enhanced by resource allocation to seed number (offspring number) or weight (offspring survival). Besides, there is a well known trade-off in resource allocation between both traits. Symbiotic interactions can influence plant resource allocation to reproduction, yet little research has been performed in this direction.We studied the consequences of a grass-fungus symbiosis on the trade-off between seed number and weight, using Lolium multiflorum and the endophyte Neotyphodium occultans as our study system. In ecological terms, we experimentally removed N. occultans from L. multiflorum plants, and compared reproductive allocation to seed number and weight in endophyte-symbiotic vs. non-symbiotic plants at different levels of nutrient availability (small pots vs. large pots). In evolutionary terms, we compared reproductive allocation between symbiotic vs. non-symbiotic plants for different host genotypes. All plants showed a negative association between seed number and weight, once standardized for total reproductive biomass. Under high nutrient availability, endophyte-symbiotic plants showed higher seed weight than non-symbiotic plants for any seed number. However, no differences were observed under low nutrient availability. Endophyte influence also varied according to L. multiflorum genotype; specifically, endophyte-symbiotic plants showed a lower slope in the relationship between seed number and weight than non-symbiotic plants for the "Marshall" genotype but no endophyte influence was found for the "Pampean" genotype. The results implied a higher plasticity in seed weight and lower plasticity in seed number for symbiotic plants. Indeed, endophyte-symbiotic plants showed an overall lower slope in the association between seed number and total reproductive biomass than non-symbiotic plants. Our results suggest that N. occultans induces heavier seeds in L. multiflorum plants under environmental conditions favorable to plant growth or for certain plant genotypes. We propose that symbiotic interactions may influence the evolution of seed number and weight trade-off.